Analisis Yuridis Tata Kelola Ketenagakerjaan Bidang Hubungan Kerja Pada Pondok Pesantren Tebuireng Jombang - Rudi Suharyanto; Rumainur Rumainur (Rumah Jurnal Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
This study explores aspects of labor governance relations in the field of work relations at the Tebuireng Islamic boarding school. Considering that this pesantren has many units, it contains many employees, especially employees who are contracted as teachers (educators). The purpose of this study was to determine the legal review of employment in Pondok Pesantren Tebuireng Jombang, East Java. This study uses a qualitative research method with a sociological juridical approach. While the data collection techniques in the study used several stages, including; First, the library (Library Research). Second, Observation, Third, Interview, and Fourth, documentation. Data analysis with data reduction steps, data presentation and drawing conclusions The results of this study indicate that in general the implementation of labor governance at the Tebuireng Islamic Boarding School is in accordance with the applicable rules, namely with a work contract, work agreements have been regulated in governance rules. staff in Islamic boarding schools.